2017
DOI: 10.1186/s12711-017-0285-6
|View full text |Cite|
|
Sign up to set email alerts
|

Application of meta-omics techniques to understand greenhouse gas emissions originating from ruminal metabolism

Abstract: Methane emissions from ruminal fermentation contribute significantly to total anthropological greenhouse gas (GHG) emissions. New meta-omics technologies are beginning to revolutionise our understanding of the rumen microbial community structure, metabolic potential and metabolic activity. Here we explore these developments in relation to GHG emissions. Microbial rumen community analyses based on small subunit ribosomal RNA sequence analysis are not yet predictive of methane emissions from individual animals o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 81 publications
1
40
0
7
Order By: Relevance
“…glycine betaine (from beet) and choline (from plant membranes), and methanol (from the hydrolysis of methanolic side-groups in plant polysaccharides) are well known [49], however the amount of these substrates might vary substantially with different diets. Previous, less temporally resolved work suggested that Methanobrevibacter was associated with high CH 4 emissions [14, 49]. However, a comparison of sheep rumen metagenomes and metatranscriptomes indicated that Methanomassiliicoccales are very active community members in both high and low CH 4 “emitters”, with around 5 times higher abundances in the metatranscriptomes compared to the metagenomes [16].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…glycine betaine (from beet) and choline (from plant membranes), and methanol (from the hydrolysis of methanolic side-groups in plant polysaccharides) are well known [49], however the amount of these substrates might vary substantially with different diets. Previous, less temporally resolved work suggested that Methanobrevibacter was associated with high CH 4 emissions [14, 49]. However, a comparison of sheep rumen metagenomes and metatranscriptomes indicated that Methanomassiliicoccales are very active community members in both high and low CH 4 “emitters”, with around 5 times higher abundances in the metatranscriptomes compared to the metagenomes [16].…”
Section: Discussionmentioning
confidence: 99%
“…[13]). In addition, the usage of meta-omics techniques has paved the way for a better understanding of the rumen ecosystem and the microbial metabolic potential and activity in the rumen (reviewed by [14]). These studies have revealed differences in rumen microbiome structure between low and high CH 4 emitting cows (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As archaeas metanogênicas desenvolveram relação simbiótica com microrganismos do rúmen mais eficientes na produção de H2, fazendo com que alberguem ao seu redor muitas bactérias metanogênicas (Tapio et al, 2017;Wallace et al, 2017). Entretanto, observa-se que em muitos estudos apenas é avaliada a abundância de determinado grupo de microrganismos sob distintas condições, sem precisar quantificar a sua importância no ambiente ruminal (Wallace et al, 2017).…”
Section: Integração Do Metabolismo Microbiano E Metanogênese Em Ruminunclassified
“…In addition to the community composition of the rumen microbiota, analysis of microbial genes in the rumen (i.e., a gene-centric approach) using metagenomic sequencing allows characterization of microbial metabolic pathways (Brulc et al, 2009;Hess et al, 2011). These DNA-based NGS approaches have facilitated characterizing "who" is there but also allows prediction of their function in the rumen (Wallace et al, 2017). However, DNA-based methods do not give information on the metabolic activity of microbes in an environment because DNA can originate from inactive or dead microbial cells (Lettat and Benchaar, 2013).…”
Section: Commonly Used Ngs-based Approaches To Characterize the Rumenmentioning
confidence: 99%